MICROSOMMITE: CRYSTAL CHEMISTRY, PHASE TRANSITIONS, ISING MODEL AND MONTE CARLO SIMULATIONS - Bonaccorsi E.; Merlino S.; Pasero M.; Macedonio G. (My University, 2001)
Microsommite, ideal formula [Na4K2(SO4)] [Ca2Cl2][Si6Al6O24], is a rare feldspathoid that occurs in volcanic products of Vesuvius. It belongs to the cancrinite–davyne group of minerals, presenting an ABAB… stacking sequence of layers that contain six-membered rings of tetrahedra, with Si and Al cations regularly alternating in the tetrahedral sites. The structure was refined in space group P63 to R=0.053 by means of single-crystal X-ray diffraction data. The cell parameters are a=22.161 Å=√3a dav, c=5.358 Å=c dav; Z=3. The superstructure arises due to the long-range ordering of extra-framework ions within the channels of the structure. This ordering progressively decreases with rising temperature until it is completely lost and microsommite transforms into davyne. The order–disorder transformation has been monitored in several crystals by means of X-ray superstructure reflections and the critical parameters T c ≈ 750 °C and β ≈ 0.12 were obtained. The kinetics of the ordering process were followed at different temperatures and the activation energy was determined to be about 125 kJ mol−1. The continuous order–disorder phase transition in microsommite has been discussed on the basis of a two-dimensional Ising model in a triangular lattice with nn (nearest neighbours) and nnn (next-nearest neighbours) interactions. Such a model was simulated using a Monte Carlo technique. The theoretical model well matches the experimental data; two phase transitions were indicated by the simulated runs: at low temperature only one of the three sublattices begins to disorder, whereas the second transition involves all three sublattices.
Keywords: CRYSTAL STRUCTURE; FELDSPATHOID; CANCRINITE-DAVYNE GROUP; PHASE TRANSITION; ORDER-DISORDER; ISING MODEL; MONTE CARLO SIMULATIONS